2021
DOI: 10.1002/jpen.2246
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition in septic shock: A pathophysiologic conundrum

Abstract: Septic shock is a public health burden and defined as a subset of sepsis whereby abnormalities in microcirculatory and cellular metabolism manifest as acute circulatory failure. At the level of the gut, septic shock impairs epithelial barrier function (EBF), and the gut initiates proinflammatory responses contributing to multiple organ dysfunction syndrome. The timing and dose of enteral nutrition (EN) in septic shock remains a conundrum. On the one hand, early EN preserves EBF. On the other hand, serious gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…Los resultados indicaron una reducción significativa en la tasa de mortalidad de aproximadamente un 19.4% y una disminución del 30% en la aparición de nuevos fallos multiorgánicos (10,11) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Los resultados indicaron una reducción significativa en la tasa de mortalidad de aproximadamente un 19.4% y una disminución del 30% en la aparición de nuevos fallos multiorgánicos (10,11) .…”
Section: Resultsunclassified
“…Cabe destacar que este estudio, en el que solo el 30% de los pacientes eran sépticos, encontró que la administración de dosis relativamente altas de glutamina aumentó la mortalidad y el riesgo de fallo multiorgánico en los pacientes. Por lo tanto, es fundamental tener en cuenta esta información al recomendar sustratos para la nutrición en pacientes con sepsis (9,11).…”
Section: Resultsunclassified
“…The results of the present study showed that care bundles resulted in significantly higher nursing efficiency and treatment compliance and a lower incidence of complications, suggesting the effectiveness of care bundles in the management of refractory septic shock. A study [18] found that patients with refractory septic shock are usually comorbid with severe circulatory impairment as well as metabolic dysfunctions, and another study [19] confirmed that intestinal dysfunction worsens in patients as their condition deteriorates, which compromises the intestinal barrier function of patients and exacerbates the inflammatory response [20]. In addition, patients receiving care bundles showed significantly lower IFABP, DAO, lactate, endotoxin, and intestinal dysfunction scores versus those with routine care, indicating that care bundles further improve intestinal barrier function and alleviate inflammatory response in patients with refractory septic shock compared to previous clinical routine care.…”
Section: Discussionmentioning
confidence: 99%
“…Septic shock related activation of immune and inflammatory pathways incites a cytokine storm [1]. Cytokines such as tumor-necrosis factor alpha (TNF-a), interleukin-1 (IL-1), and interleukin-6 (IL-6) promote breakdown of barrier defenses [18,19].…”
Section: The Conundrum Of Introducing Luminal Nutrients In Septic Shockmentioning
confidence: 99%
“…The benefits from bathing the mucosa (with enteral nutrition) include supporting the population of the commensal microbiome, maintaining gut barrier defenses, and promoting a robust but appropriate immune response. Failing to take advantage of introducing enteral nutrition results in adverse consequences from not using the gut [18,19].…”
Section: The Conundrum Of Introducing Luminal Nutrients In Septic Shockmentioning
confidence: 99%